A CAUSAL MODEL OF ADMINISTRATIVE FACTORS AFFECTING EDUCATIONAL QUALITY IN VOCATIONAL SCHOOLS: QUALITATIVE EMPIRICAL EVIDENCE - Kraikunasai, Jutamanee; Chongcharoen, Koolchalee; Ngudgratoke, Sungworn; Pukchanka, Pronanchalee (PEOPLE: International Journal of Social Sciences, 2017)
The purposes of this study were to develop the causal model of administrative factors affecting educational quality in vocational schools and to analyze the key administrative factors affecting educational quality in vocational schools. This study employed a mixed-method research design comprising a qualitative data analysis of literature review on the administrative factors affecting educational quality, efficiency, and effectiveness followed by in-depth interviews and a quantitative data analysis of the extensive empirical survey. The sample for the interviews was 30 purposive participants which were 6 administrators, 18 teachers of selective schools, and 6 policymakers at the administrative level. The qualitative data analysis of the interviews confirmed the factors in the conceptual framework and provided the key behavioral definition to be used to create the questionnaire. Later, the quantitative data analysis will continue by using descriptive analysis, confirmatory factor analysis, and SEM Analysis. The most significant key theme emerging from the results is the key administrative factors affecting educational quality in vocational schools: 1) Transformational Leadership 2) School Culture Strength 3) Resource Management Quality and 4) Learning Management Quality, which could be the preliminary evidence suggesting how to accomplish educational quality in vocational schools in Thailand.